2012
DOI: 10.1111/j.1469-0691.2012.03858.x
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline resistance genes and mobile genetic elements from the oral metagenome

Abstract: Tetracycline resistance genes are common in the human oral cavity. However, a complete understanding of tetracycline resistance and the vectors responsible for spread of resistance requires that we understand the contribution of organisms that cannot be cultivated in the laboratory. To do this, metagenomic approaches have been applied and this has allowed the isolation of novel tetracycline resistance genes and mobile genetic elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Metagenomic analysis and massive sequencing techniques have been used to monitor antibiotic resistance genes in environmental (Hatosy and Martiny, 2015), animal (Kazimierczak et al, 2009), and human ecosystems (Diaz-Torres et al, 2003; Seville et al, 2009; Mullany et al, 2012; Forslund et al, 2014), and would appear promising as means of characterizing the same in dairy environments. These techniques allow for the molecular characterization of the resistance genes and their associated genetic elements; this may further help to estimate the risk for their horizontal transference.…”
Section: Introductionmentioning
confidence: 99%
“…Metagenomic analysis and massive sequencing techniques have been used to monitor antibiotic resistance genes in environmental (Hatosy and Martiny, 2015), animal (Kazimierczak et al, 2009), and human ecosystems (Diaz-Torres et al, 2003; Seville et al, 2009; Mullany et al, 2012; Forslund et al, 2014), and would appear promising as means of characterizing the same in dairy environments. These techniques allow for the molecular characterization of the resistance genes and their associated genetic elements; this may further help to estimate the risk for their horizontal transference.…”
Section: Introductionmentioning
confidence: 99%
“…Culture-independent analysis is also faster and more accurate than culture-based methods. Indeed, several AR identification and AR gene quantification techniques that require no culturing have recently been developed, such as denaturing gradient gel electrophoresis (DGGE) [ 15 , 16 ], real-time quantitative PCR (qPCR) [ 13 , 14 , 17 ], construction and functional analysis of gene libraries [ 18 20 ], AR gene microarrays [ 21 , 22 ], and analysis of metagenomic sequences [ 23 , 24 ]. Knowledge of the types and loads of AR genes in foods could ultimately be of help to estimate the risk of their transmission during cheese manufacturing and after consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The high percentage of tetracycline and quinolone resistance genes might be caused not only by antibiotic selection pressure, but also by horizontal transmission due to high-density feeding pattern. More and more evidences showed that the MGEs was an important way in the mechanism of resistance to tetracycline and quinolones (47) (48)(49)(50). On the other hand, there was a correlation between these ARGs that might lead to multidrug resistance.…”
Section: Discussionmentioning
confidence: 99%